Development of High‐Capacity and Water‐Lean CO2 Absorbents by a Concise Molecular Design Strategy through Viscosity Control. Issue 23 (18th November 2019) - Liu, An‐Hua; Li, Jie‐Jie; Ren, Bai‐Hao; Lu, Xiao‐Bing
Abstract: The exponentially increasing viscosity of water‐lean CO2 absorbents during carbon capture processes is a critical problem for practical application, owing to its strong correlation with systems' mass transfer properties, as well as convenience of transportation. In this work, a concise strategy based on structure–viscosity relationships is proposed and applied to construct a series of functionalized ethylenediamines as single‐component absorbents for post‐combustion CO2 capture. These nonaqueous absorbents have outstanding viscosities (50–200 cP, 25 °C) at their maximal CO2 capacities (up to 22 wt % or 4.92 mol kg −1, 1 bar), and are readily regenerated at low temperatures (50–80 °C) under ambient pressure. Additional capture of CO2 through physisorption could also be achieved by operating at high pressures. The CO2 capture and release process is systematically investigated by means of 13 C NMR spectroscopy, differential scanning calorimetry (DSC), in situ FTIR analysis, and density functional theory (DFT) calculations, which could provide sufficient spectroscopic details to reveal the ease of reversibility and enable rational interpretation of the absorption mechanism. Abstract : You shall know our viscosity : Functionalized ethylenediamines are applied as water‐lean CO2 absorbents with high capacity and low viscosity. The success of these single‐component absorbents can be attributed to a concise two‐step molecular design strategy that involves the introduction of alkoxyethyl and the replacement of unnecessary N−H bonds by N−Me, to prevent the viscosity increase of CO2 ‐bonded ethylenediamines.